Encouraging Performance Behavior Bhinneka Foundation Teacher Boyolali Works - Unna Ria Safitri (STIE AUB Surakarta, 2018)
A large organization, it will cause various problems faced by organizations, especially in the field of management. Leadership plays an important role in improving employee performance. Without leadership and guidance, an organization cannot be achieved according to its objectives. Bhinneka Karya Boyolali Foundation arises a problem, among them is the decreasing performance of the teacher due to lack of availability of facilities and infrastructure that support teacher performance, leadership factors also affect teacher performance, because the success of an organization depends on leadership quality that is able to motivate, direct, influence and communicate with subordinates so that the goals of the organization can be achieved optimally. This study aims to analyze the Effect of Leadership and Work Environment on Employees Through Job Satisfaction (Case Study on Teachers of Bhinneka Karya Boyolali Foundation). This study uses the instrument test analysis method which includes validity and reliability test, linearity test, regression analysis, path analysis, namely direct influence, indirect influence and total influence. T test, F test, test the coefficient of determination and correlation analysis. From the results of the questionnaire obtained Hypothesis Test Results are: Leadership has a significant effect on job satisfaction. The work environment has a significant effect on employee job satisfaction. Leadership has a significant effect on performance, the work environment has a significant effect on employee performance. F test results are known to be the value of F = 101.998 sig 0.000 <0.05. So that it can be concluded together leadership, work environment and job satisfaction have a significant effect on the performance of employees at the Bhinneka Karya Boyolali Foundation Teachers. The total R2 value of 0.970 means that the variation of employee performance in the teachers of various foundation boyolali works is explained by the variables of leadership, work environment and job satisfaction by 97.0% and the remaining 3.0% are explained by other variables outside the research model. It is known that the results of the analysis of the work environment path to performance is an effective pathway to improve performance.Keywords: Leadership, work environment, job satisfaction, employee performance